Stabilisers for water-in-fluorinated-oil dispersions: Key properties for microfluidic applications. Issue 3 (June 2015) - Gruner, Philipp; Riechers, Birte; Chacòn Orellana, Laura Andreina; Brosseau, Quentin; Maes, Florine; Beneyton, Thomas; Pekin, Deniz; Baret, Jean-Christophe
Abstract Droplet-based microfluidics appears as a key emerging technology for the miniaturization and automation of biochemical assays. In terms of technology, it stands on two basic pillars: microfluidic devices on the one hand and emulsions on the other hand. Huge progress has been made on large scale integration of devices and batch production of devices. The limiting factor for a full application of the technology is actually not device development, but rather the robust control of emulsion formulations to be used in these devices. We here review the basic problems related to emulsions relevant for microfluidic applications and open up on new promising applications for these systems.